Post-totalitarian societies in transformation : from systemic change into European integration - Mach, Zdzisław 1954- HerausgeberIn; Mach, Elżbieta 1965- HerausgeberIn; Pożarlik, Grzegorz HerausgeberIn; Sondel-Cedarmas, Joanna 1975- HerausgeberIn (Studies in European Integration, State and Society, 2022)
This study considers the multidimensional nature of the construction of the active civil society in the post-totalitarian reality of Central and Eastern Europe, covering the period of systemic transformations in the region in 1989 to the EU accession of 2004. The analysis was carried out using a multidisciplinary research perspective which incorporates historical, sociological, and legal insights, as well as those from political science. The volume illustrates the dynamic character of the process of constructing an active civil society process in a broader comparative perspective against the background of post-totalitarian societies, Germany and Italy, which underwent the process of democratic transformation in 1945 and went on to actively forge the European Community in the 1950s.